(untitled) (Comprehensive Journal of Science, 2026)
This study addresses the concept of anticipatory self-defense in international law by analyzing its legality and legal limits in light of the rules of contemporary international law. It aims to clarify the legal framework governing Article 51, which affirms the right of states to self-defense in the event of an armed attack, as an exception to the principle of the prohibition of the use of force set forth in Article(2/4) . The study also examines the doctrinal and legal debate surrounding anticipatory self-defense, between a restrictive view that rejects this concept due to its inconsistency with the provisions of the Charter, and a permissive view that recognizes its applicability in cases of extreme necessity and imminent threat, as well as reviewing state practice related to this form of self-defense.